(untitled) (The Pakistan Development Review, 2002)
(1) Pakistan is lucky in having internationally recognised political and philosophical role models in the shape of Quaid-i-Azam and Allama Muhammad Iqbal. (2) Both of them were Founders of Pakistan and had their own vision of the way Pakistan’s society and economy was to be shaped—a society based on true Islamic concept of equality of manhood and social justice. (3) Pakistan, inspite of making many infrastructural advances, has not developed a truly modern, democratic, welfare society. This goal can be achieved more effectingly if we follow the footsteps of both Quaid-i- Azam and Allama Muhammad Iqbal because both of them lived among public, understood the shortcomings and potentials of their community, and were familiar with the multidimensional process involving major changes in social structures, popular ideas, and national character and institutions as well as historical and cultural psyche: of Pakistan nation. (4) Note the following instructions which Quaid-i-Azam gave to the State Bank of Pakistan on 1st July 1948: